Characteristics of Gender, Age, Spatial and Temporal Distribution of Stroke Hospitalization Cases Based on the Data of 190 000 Patients in Ningxia Region - ZHAO Yuan, LIU Shanghong, ZHANG Yanfang, MA Lixu, LI Hong, LI Xiaohua, TIAN Yuan, GUO Zhongqin, LIANG Peifeng (Zhongguo quanke yixue, 2024)
Background Stroke is an acute cerebrovascular disease in which blood fails to flow into the brain, resulting in damage to brain tissue, with high rates of disability, death, and recurrence, and most of the related studies in Ningxia region are clinical analyses of strokes, which lack trend analysis of stroke hospitalization in Ningxia in recent years. Objective To analyze the disease prevalence characteristics and distribution of stroke hospitalized patients in Ningxia, and provide a basis for the development of comprehensive prevention and treatment measures for stroke. Methods The case home page data of 55 hospitals of traditional Chinese medicine (TCM) and western medicine in Ningxia region were collected, and the data discharged from 2013 to 2019 with a primary diagnosis of stroke [International Classification of Diseases (ICD) -10 coded as I60-I63] were screened and analyzed. SPSS 24.0 software was applied to analyze the differences in gender and age using the chi-square test, and a geographic information system (GIS) was applied to analyze the distribution of stroke hospitalization rate data across Ningxia from 2013 to 2019 using global spatial auto correlation analysis. Results A total of 190 634 stroke patients were finally included. The hospitalization rate of stroke in Ningxia region showed an increasing trend year by year from 2013 to 2019 (hospitalization rates of 24.302/10 000, 30.045/10 000, 34.949/10 000, 39.397/10 000, 44.049/10 000, 47.617/10 000, and 52.944/10 000, respectively, χ2trend=5.982, P=0.014) , and the hospitalization rates were higher during the cold season of each year, with a significant peak in March and a slight decline thereafter. Among the stroke inpatients in Ningxia from 2013 to 2019, there were 167 194 cases of ischemic stroke and 23 440 cases of hemorrhagic stroke; there was significant difference between ischemic stroke and hemorrhagic stroke patients in gender and age (χ2=473.533, 7 518.543, P<0.05) ; and the proportion of male, ≥60 years old hospitalized patients in ischemic stroke and hemorrhagic stroke exceeded 50% from the data. The results of global auto correlation analysis showed spatial aggregation of stroke hospitalization rates in 2013, 2018 and 2019 (P<0.05) . The spatial distribution map showed that the hospitalized stroke patients in Ningxia were mainly concentrated in north-central Ningxia. Conclusion From 2013 to 2019, the hospitalization rate of stroke patients in Ningxia showed increasing and varying degrees of aggregation, and the areas with higher hospitalization rates were concentrated in north-central Ningxia.